PERLINDUNGAN HUKUM PEMEGANG HAK ATAS TANAH DALAM PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Muhammad Yusrizal (Universitas Muhammadiyah Sumatera Utara, 2017)
Land procurement is the act of the government to realize the availability of land to be used in various interests for development as the public interest. Limitations of land owned by the government takes the land derived from the community to facilitate the course of development for the public interest. The existence of the land needs to be used by the government in carrying out development activities, but in its implementation should not be detrimental to the rights of the landowners. Therefore, for the government which needs the land can not arbitrarily to take the land belonging to the community/the holder of the right to the land which area is affected by development for the public interest. Therefore, the state should provide guarantee and legal protection to the holder of the land in land procurement activity for public interest. So that the implementation of land procurement will be able to provide a sense of justice for the community affected by the development and provide security to the life of the community.